Penerapan dan Hambatan Pelayanan Publik Undang-Undang Nomor 25 Tahun 2009 Pada Pembuatan Surat Izin Mengemudi Pengendara Roda Dua di Satuan Lalu Lintas Kepolisian Resor Kendal - Farhandito, Tangguh; Listyarini, Dyah; Suliantoro, Adi (Wajah Hukum, 2024)
Public services in Indonesia, in general, remain disappointing. Despite various regulations implemented to enhance the quality of public services, it seems to have not significantly impacted the society. Violations committed by government employees also show no decline, and in fact, tend to occur more frequently. This research discusses the raised issues using a juridical-empirical approach, with an emphasis on legal aspects as a manifestation of society's attitude toward law and the legal system. This can be considered as an example of values, ideas, beliefs, or expectations that ultimately determine the extent to which the law is followed, violated, or deviated. In other words, it can be referred to as a juridical-sociological approach where the law is not only seen as rules or regulations but also involves the implementation of the law within society. The research findings indicate that the implementation of Law Number 25 of 2009 on Public Services at the Traffic Unit of Kendal Police Resort runs effectively. Officers at Kendal Police Resort, in carrying out the task of issuing Driving Licenses (SIM), operate in accordance with the prevailing regulations. Several residents intending to obtain a SIM choose not to immediately utilize middlemen services because the police officers are ready to assist them fully.